2021
DOI: 10.3390/vaccines9101057
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Quarterly Sow Mass Vaccination with a Porcine Reproductive and Respiratory Syndrome Virus Type 1 (PRRSV-1) Modified Live Vaccine in Two Herds

Abstract: In recent years, there has been a considerable increase in the use of Modified Live PRRSV Vaccines (MLV) for mass vaccination in Denmark. The potential risks and negative impact of this strategy have been sparsely studied. The aim of this study was to investigate the impact of quarterly sow mass vaccination in two Danish sow herds. The study was performed as an observational prospective cohort of 120 sows in each of two commercial breeding herds in a paired design. Blood samples were taken from sows and oral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…Recently, our research group has assessed the prevalence of these multiple PRRSV-vaccinated but ELISA seronegative sows in Belgium; a global prevalence of 3.5% to 4.1% of non-responding sows was found [ 14 ]. Similar observations of anergic sows after repeated PRRSV vaccination were reported at the same time by other research groups, with the global prevalence ranging from 1% to 4% [ 15 , 16 ]. A first consequence of this sow seronegative status for the progeny has been assessed in a follow-up study [ 17 ].…”
Section: Introductionsupporting
confidence: 87%
“…Recently, our research group has assessed the prevalence of these multiple PRRSV-vaccinated but ELISA seronegative sows in Belgium; a global prevalence of 3.5% to 4.1% of non-responding sows was found [ 14 ]. Similar observations of anergic sows after repeated PRRSV vaccination were reported at the same time by other research groups, with the global prevalence ranging from 1% to 4% [ 15 , 16 ]. A first consequence of this sow seronegative status for the progeny has been assessed in a follow-up study [ 17 ].…”
Section: Introductionsupporting
confidence: 87%
“…One of the boars in the early infected group did not seroconvert after virus exposure, which has previously been described in vaccine trials ( Díaz et al, 2020 ; Pedersen et al, 2021 ). However, this result could also be false negative due to the relative high dilution of the serum in the ELISA or the boar could have had antibodies other than N protein detectable antibodies, e.g., neutralising antibodies.…”
Section: Discussionsupporting
confidence: 51%
“…Unfortunately, the effectiveness of PRRSV vaccination is suboptimal, mainly due to the large genetic diversity of the virus and its capability to modulate the immune response [ 14 , 15 , 16 ]. Additionally, several studies reported the unsuccessful PRRSV vaccination of both piglets and sows, resulting in seronegative animals despite vaccination [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Our research group aimed to unravel the role of these non-responding animals by assessing their prevalence, origin, and possible consequences [ 26 , 27 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, the limited production of neutralizing antibodies and the low induction of PRRSV-specific interferon-γ secreting cells are responsible for the lack of protective immunity [ 22 , 23 , 24 , 25 ]. Finally, it has been shown that a proportion of PRRSV-vaccinated sows and/or piglets lack a PRRSV-specific antibody response, with vaccinated pigs remaining seronegative in commercial ELISA kits [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In multivaccinated sows, the origin of this non-responsiveness upon vaccination remains unknown and warrants further investigation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%